2015
DOI: 10.1111/jeb.12764
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to deer herbivory and resistance to insect herbivores in the common evening primrose (Oenothera biennis)

Abstract: The evolution of plant defence in response to herbivory will depend on the fitness effects of damage, availability of genetic variation and potential ecological and genetic constraints on defence. Here, we examine the potential for evolution of tolerance to deer herbivory in Oenothera biennis while simultaneously considering resistance to natural insect herbivores. We examined (i) the effects of deer damage on fitness, (ii) the presence of genetic variation in tolerance and resistance, (iii) selection on toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…As well, some species of Oenothera may have evolved alternative defensive strategies in different biogeographic regions, such as greater investment in induced defenses (Anstett et al. ), tolerance (Puentes and Johnson ), or avoidance (Agrawal et al. ), which could obscure latitudinal gradients in constitutive defenses like those studied here.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As well, some species of Oenothera may have evolved alternative defensive strategies in different biogeographic regions, such as greater investment in induced defenses (Anstett et al. ), tolerance (Puentes and Johnson ), or avoidance (Agrawal et al. ), which could obscure latitudinal gradients in constitutive defenses like those studied here.…”
Section: Discussionmentioning
confidence: 73%
“…These mechanisms are not mutually exclusive, and could lead to complex patterns of selection across space that do not closely follow latitudinal gradients. As well, some species of Oenothera may have evolved alternative defensive strategies in different biogeographic regions, such as greater investment in induced defenses (Anstett et al 2016a), tolerance (Puentes and Johnson 2016), or avoidance , which could obscure latitudinal gradients in constitutive defenses like those studied here.…”
Section: Colder Climates?mentioning
confidence: 80%
“…Oenothera biennis preferentially occupies open and disturbed habitats (e.g. fields, roadsides, and lakeshores) ( Puentes and Johnson, 2016 ), and severely damages the local natural ecosystem ( Thijs et al., 2012 ). Previous studies have confirmed that high leaf area, the reproductive period in late summer, and long roots were key traits for the successful colonization of invasive O. biennis ( Stanisci et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, these resources allowed the first test in plants of multiple predictions stemming from theory of the evolution of sex [40,[44][45][46][47][48][49][50][51]. Recent research also led to important advances in the study of plant defense evolution [52][53][54][55][56][57][58][59], and eco-evolutionary dynamics within communities [60][61][62][63][64][65][66][67][68]. Further, genomic tools have made it possible to determine the role of nuclear-organellar incompatibilities in speciation [69,70], mechanisms of mutations in plastid genome evolution [71], novel mechanisms in chloroplast gene expression [72], and the identification of chloroplast genes involved in plastid transmission [73].…”
Section: Introductionmentioning
confidence: 99%